Psoromic Acid, a Lichen-Derived Molecule, Inhibits the Replication of Hsv-1 and Hsv-2, and Inactivates Hsv-1 Dna Polymerase: Shedding Light on Antiherpetic Properties - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Psoromic acid (PA), a bioactive lichen-derived compound, was investigated for its inhibitory properties against herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2), along with the inhibitory effect on HSV-1 DNA polymerase, which is a key enzyme that plays an essential role in HSV-1 replication cycle. PA was found to notably inhibit HSV-1 replication (50% inhibitory concentration (IC50): 1.9 μM; selectivity index (SI): 163.2) compared with the standard drug acyclovir (ACV) (IC50: 2.6 μM; SI: 119.2). The combination of PA with ACV has led to potent inhibitory activity against HSV-1 replication (IC50: 1.1 μM; SI: 281.8) compared with that of ACV. Moreover, PA displayed equivalent inhibitory action against HSV-2 replication (50% effective concentration (EC50): 2.7 μM; SI: 114.8) compared with that of ACV (EC50: 2.8 μM; SI: 110.7). The inhibition potency of PA in combination with ACV against HSV-2 replication was also detected (EC50: 1.8 μM; SI: 172.2). Further, PA was observed to effectively inhibit HSV-1 DNA polymerase (as a non-nucleoside inhibitor) with respect to dTTP incorporation in a competitive inhibition mode (half maximal inhibitory concentration (IC50): 0.7 μM; inhibition constant (Ki): 0.3 μM) compared with reference drugs aphidicolin (IC50: 0.8 μM; Ki: 0.4 μM) and ACV triphosphate (ACV-TP) (IC50: 0.9 μM; Ki: 0.5 μM). It is noteworthy that the mechanism by which PA-induced anti-HSV-1 activity was related to its inhibitory action against HSV-1 DNA polymerase. Furthermore, the outcomes of in vitro experiments were authenticated using molecular docking analyses, as the molecular interactions of PA with the active sites of HSV-1 DNA polymerase and HSV-2 protease (an essential enzyme required for HSV-2 replication) were revealed. Since this is a first report on the above-mentioned properties, we can conclude that PA might be a future drug for the treatment of HSV infections as well as a promising lead molecule for further anti-HSV drug design. © 2019 MDPI AG. All rights reserved.